6~35kV anti-water-tree copper core cross-linked polyethylene insulated cable

CN122800347APending Publication Date: 2026-09-22GUANGDONG SHINE CABLES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610874587.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

在高温交联工艺的过程中,为了防止高温交联过程中产生气泡一般会用1~2MPa的氮气加压,但是还是很难完全抑制聚乙烯层内部产生微小起泡、或原本存在的微小起泡受热涨大,最后在冷却的过程中产生的缝隙

Benefits of technology

[0027]第一,关于本发明的高密度聚乙烯包覆母粒的特点:1. 适合添加量的乙烯基硅烷偶联剂不会将纳米滑石粉的表面完全改性,既能够保持纳米滑石粉的成核特性,又能够抑制纳米滑石粉团聚并提滑石粉与树脂基体的结合性以减少空隙;2. 纳米滑石粉在熔融挤出工艺中能够促使聚乙烯树脂基体排出空气进一步提高致密性;3. 乙烯基硅烷偶联剂相比于其它硅烷偶联剂具有更好的交联和促进分散效果;4. 合适的表面改性工艺温度,能够促进接枝、抑制团聚;5. 高密度聚乙烯作为包覆树脂,与交联聚乙烯的树脂基体一致,保证与树脂基体的相容性;6. 加入特定含量的聚乙烯蜡作为润滑剂,可能是由于其与高密度聚乙烯熔点相近,相比于本领域中常用的其它润滑剂可以进一步减少填料团聚和填料与树脂基体之间的空隙;7. 通过冷冻粉碎得到D50粒径30~100微米的颗粒,使填料均匀分散到树脂基体中,促进成核、改善耐磨。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800347A_ABST
    Figure CN122800347A_ABST
Patent Text Reader

Abstract

The application discloses a 6-35kV water treeing resistant copper core crosslinked polyethylene insulated cable, which is composed of single insulated cable core or multiple insulated cable cores twisted together, and the insulated cable core is sequentially composed of a copper wire core, a semi-conductive shielding layer, a crosslinked polyethylene water treeing resistant insulation layer, an insulation shielding layer and a metal shielding layer; the single-core cable is sequentially composed of an isolation sleeve, a metal armor layer and a crosslinked polyethylene water treeing resistant sheath outside the insulated cable core; and the multi-core cable is sequentially composed of a filler layer, a tightening belt, a metal armor layer and a crosslinked polyethylene water treeing resistant sheath outside the insulated cable core. The water treeing resistant function of the cable is mainly derived from the crosslinked polyethylene water treeing resistant insulation layer and the crosslinked polyethylene water treeing resistant sheath, and the sheath also has the advantage of wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable technology, and in particular to a 6-35kV water-tree resistant copper core cross-linked polyethylene insulated cable. Background Technology

[0002] Currently, my country is implementing large-scale upgrades and renovations to urban and rural power grids and communication facilities, creating a significant demand for wires and cables. The growth of water trees within the cable insulation layer is a major factor affecting cable performance. Conventional cross-linked polyethylene materials struggle to overcome this technical bottleneck.

[0003] Water treeing is a degradation process observed in cross-linked polyethylene (XLPE) and other cable insulation materials under alternating current stress and humid conditions, resulting in the formation of so-called water tree dielectric weakening zones. Water trees are hydrophilic, dendritic features (in particular, initially appearing as chain-like water-filled cavities, later forming dendritic microchannels with hydrophilic surfaces). Under humid conditions and electrical stress, water trees can grow to approximately 1 mm in size over several years. Essentially, it is the result of the synergistic effect of moisture intrusion and electrical stress. Generally, the higher the water absorption of XLPE, the easier it is to provide a medium for water treeing. However, researchers have found in numerous experiments that a low water absorption rate does not necessarily indicate good resistance to water treeing. Besides improving the density of XLPE, resistance to water treeing also requires low surface roughness, uniform dispersion of a small number of crystalline and cross-linked regions within the resin matrix, good dispersion of fillers (if any), and no gaps or bubbles between the fillers and the resin to reduce water treeing channels. During the high-temperature cross-linking process, nitrogen gas at 1-2 MPa is typically used to pressurize the process and prevent the formation of bubbles. However, it is still difficult to completely suppress the formation of micro-bubbles within the polyethylene layer, or the expansion of existing micro-bubbles due to heat, ultimately leading to gaps during cooling. This is especially true in cross-linked polyethylene sheaths with added fillers (talc, calcium carbonate, montmorillonite, etc.), where the micropores between the filler and resin easily become the core of expansion during the high-temperature cross-linking reaction. These micro-bubbles then collapse during cooling, creating defects such as pores and gaps, making it difficult to improve water-tree resistance. Therefore, a further challenge with existing technology lies in the difficulty of producing cross-linked polyethylene cable sheaths that simultaneously possess wear resistance (especially when containing a large amount of filler) and water-tree resistance.

[0004] In the prior art, methods for improving the water-tree resistance of cross-linked polyethylene include: Chinese authorized patent 202510602580X discloses a medium-voltage cable with water-tree resistance. The raw materials of its cross-linked polyethylene insulation layer include polyethylene, water-tree resistance masterbatch, cross-linking agent, and processing aid. The raw materials of the water-tree resistance masterbatch include polyethylene, copolymer, and inorganic porous granules. The copolymer is poly(butadiene-vinylpyridine) and / or poly(vinylphosphonic acid) with a mass ratio of 100:3~7:15~25 and an RWTG value range of 20~30. However, due to the poor compatibility between the above copolymer and polyethylene, and the fact that the masterbatch contains inorganic porous granules which easily contain air in the pores and generate bubbles during the high-temperature cross-linking process, the water-tree resistance performance is deteriorated. Therefore, this patented formula is significantly affected by processing conditions and has poor experimental reproducibility. Chinese patent 200610028831.5 discloses a water-tree resistant polyolefin electrical insulation composition containing 100 phr of polyethylene matrix resin, 2 phr of crosslinking agent, 0.2~0.6 phr of sugar alcohol polymers (sorbitol, xylitol, mannitol, erythritol) as water-tree resistant growth agents, and 3~8 phr of polyethylene-based copolymers (ethylene-vinyl acetate copolymer, ethylene-acrylate copolymer). The RWTG value ranges from 10 to 25. However, it is difficult to expand the wear resistance of this patented technology. Summary of the Invention

[0005] The purpose of this invention is to avoid the above-mentioned technical defects and provide a 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable with good water tree resistance. It also provides a raw material formula for a cross-linked polyethylene waterproof tree insulation layer and a raw material formula for a cross-linked polyethylene waterproof tree wear-resistant sheath.

[0006] The above-mentioned objective of the present invention is achieved through the following technical solution:

[0007] A 6-35kV water-resistant resin-resistant copper core cross-linked polyethylene insulated cable is disclosed. The cable is composed of a single insulated core (single core) or multiple insulated cores (e.g., three cores) twisted together. From the inside out, the insulated core consists of a copper wire core 1, a semi-conductive shielding layer 2, a cross-linked polyethylene waterproof resin insulation layer 3, an insulating shielding layer 4, and a metal shielding layer 5. Outside the insulated core of a single-core cable, there is an isolation sleeve 6, a metal armor layer 9, and a cross-linked polyethylene waterproof resin sheath 10. Outside the insulated core of a multi-core cable, there is a filler layer 7, a binding tape 8, a metal armor layer 9, and a cross-linked polyethylene waterproof resin sheath 10. The raw material of the cross-linked polyethylene waterproof resin insulation layer is specified by weight percentage. The raw materials of the cross-linked polyethylene waterproof and wear-resistant sheath, calculated by weight percentage, include: 92-97.5% high-density polyethylene, 1-2% peroxidation crosslinking initiator, 1-5% high-density polyethylene coated with nano-talc masterbatch with a D50 particle size of 30-100 micrometers, 0.5-1% antioxidant, and 0-1% crosslinking aid;

[0008] The peroxidation crosslinking initiator is one or more of bis-tert-butyl peroxide, diisopropylbenzene peroxide, diisopropylbenzene peroxide, diisopropylbenzene peroxide, and lauroyl peroxide; the antioxidant is a hindered phenolic antioxidant (such as antioxidant 1010) and a phosphite antioxidant (such as antioxidant 168) in a mass ratio of (2~4):1; the additives are UV stabilizers, colorants, or pigments; the crosslinking aid is one or more of triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate, and trimethylolpropane triacrylate; and the density range of the high-density polyethylene is 0.940~0.970 g / cm³. 3 .

[0009] The nano-talc masterbatch, calculated by weight percentage based on high-density polyethylene coated with nano-talc powder with a D50 particle size of 30-100 micrometers, includes: 40-50% high-density polyethylene, 0.3-0.8% vinyl silane coupling agent, 40-50% nano-talc powder, and 5-10% polyethylene wax. The weight ratio of nano-talc powder to vinyl silane coupling agent is (60-150):1. The preparation process is as follows: first, nano-talc powder and vinyl silane coupling agent are mixed in a mixer at 60-90℃ for 0.5-3 hours. Then, it is extruded and granulated with polyethylene wax and high-density polyethylene through an extruder. The barrel temperature range is 120-140℃. After cooling, it is obtained by cryogenic pulverization (below -150℃, such as freezing with liquid nitrogen and pulverizing with a low-temperature pulverizer) and sieving.

[0010] The D50 particle size of the masterbatch was tested using a laser particle size analyzer.

[0011] The composition, calculated by weight percentage of high-density polyethylene coated with nano-talc powder and chopped basalt fiber masterbatch with D50 particle size of 30-100 micrometers, includes: 30-50% high-density polyethylene, 30-50% nano-talc powder, 5-10% chopped basalt fiber, 1-2% vinyl silane coupling agent, and 5-10% polyethylene wax. The weight ratio of nano-talc powder to vinyl silane coupling agent is (60-150):1. The preparation process is as follows: nano-talc powder and vinyl silane coupling agent are mixed in a mixer at 60-90℃ for 0.5-3 hours, chopped basalt fiber and vinyl silane coupling agent are mixed in a mixer at 60-90℃ for 0.5-3 hours, and then extruded with high-density polyethylene and polyethylene wax through an extruder for granulation. The barrel temperature range is 120-140℃. After cooling, the mixture is cryogenically pulverized (below -150℃, for example, by liquid nitrogen freezing) and sieved to obtain the final product.

[0012] Since the amount of vinylsilane coupling agent added is small, in order to improve the uniformity of surface modification, it can be diluted 5 to 20 times with an aqueous alcohol solution, such as an aqueous ethanol solution, an aqueous isopropanol solution, an aqueous methanol solution, etc., with an alcohol:water volume ratio of (6 to 9):1. After mixing evenly, it is kneaded, and the solvent is evaporated during the kneading process.

[0013] The semiconductive shielding layer 2 and the insulating shielding layer 4 can be conventional cross-linked formulations in the art. Commonly used cross-linked ethylene conductor shielding layers in the art can contain 30-60% polyethylene resin, 10-40% EVA, 10-40% conductive carbon black, 0.5-1.5% cross-linking agent, 0.5-1.5% co-cross-linking agent, etc., and may also contain other additives such as antioxidants. The content of each component is mainly adjusted according to the volume resistivity requirements. The function of the semiconductive shielding layer 2 is to uniformly wrap the copper wire core, eliminate electric field distortion caused by burrs on the surface of the copper wire core, and prevent partial discharge. The function of the insulating shielding layer 4 is to adhere tightly to the outside of the insulating layer, balance the external electric field, and is part of a double-layer shielding system (insulating shielding layer + metal shielding layer).

[0014] The vinyl silane coupling agent is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and vinyltritert-butylperoxysilane.

[0015] The filler 7 can be refractory filler or filler rope. The refractory filler can be near-circular refractory filler particles, and the filler rope can be glass water-blocking yarn. If glass water-blocking yarn is used as filler 7, an additional layer of mica refractory strip can be added to improve the refractory performance.

[0016] The metal shielding layer 5 is a copper fiber braided tape.

[0017] The isolation sleeve 6 can be made of cross-linked polyethylene or other materials.

[0018] The metal armor layer 9 can be an aluminum-plastic composite strip or a non-magnetic stainless steel strip, which serves as a component of the armor layer and provides protection and waterproofing.

[0019] The manufacturing process of the 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable of this invention is as follows (taking a single core as an example):

[0020] 1) Using a copper wire core as the core, it is co-extruded with a semi-conductive shielding layer, a cross-linked polyethylene waterproof resin insulation layer, and an insulating shielding layer. Then, it is cross-linked under a pressure of 260~320℃ and nitrogen pressure of 1~1.5MPa (if the thickness is too thick, each layer can be extruded and cross-linked sequentially).

[0021] 2) Wrap a metal shielding layer around the core to obtain an insulated cable core;

[0022] 3) Finally, the isolation sleeve, the metal armor layer, and the cross-linked polyethylene waterproof and wear-resistant sheath are extruded and then cross-linked under the above conditions to obtain a single-core product.

[0023] The extrusion temperature range for the materials of the semi-conductive shielding layer and insulating shielding layer, the cross-linked polyethylene waterproof resin insulating layer, and the sheath is 120~150℃.

[0024] The present invention also provides a raw material for a cross-linked polyethylene waterproof resin insulation layer, which, by weight percentage, comprises: 92-97.5% high-density polyethylene, 1-2% peroxidation cross-linking initiator, 1-5% high-density polyethylene coated nano-talc masterbatch with a D50 particle size of 30-100 micrometers, and 0.5-1% antioxidant.

[0025] The present invention also provides a raw material for a cross-linked polyethylene waterproof and wear-resistant sheath, which, by weight percentage, comprises: 82-94% high-density polyethylene, 0.5-2% peroxidation cross-linking initiator, 5-15% high-density polyethylene coated with nano-talc powder and short-cut basalt fiber masterbatch with D50 particle size of 30-100 micrometers, 0.5-1% antioxidant, and 0-2% additives.

[0026] The technical measures of this invention have the following advantages compared with the prior art:

[0027] First, regarding the characteristics of the high-density polyethylene coated masterbatch of the present invention: 1. The appropriate amount of vinyl silane coupling agent added does not completely modify the surface of nano-talc powder, thus maintaining the nucleation characteristics of nano-talc powder while inhibiting its agglomeration and improving the bonding between talc powder and the resin matrix to reduce porosity; 2. Nano-talc powder can promote the expulsion of air from the polyethylene resin matrix during melt extrusion, further improving its density; 3. Vinyl silane coupling agent has better crosslinking and dispersion-promoting effects compared to other silane coupling agents; 4. A suitable surface modification process temperature can promote grafting and inhibit agglomeration; 5. High-density polyethylene, as the coating resin, is consistent with the resin matrix of crosslinked polyethylene, ensuring compatibility with the resin matrix; 6. The addition of a specific amount of polyethylene wax as a lubricant is likely due to its similar melting point to high-density polyethylene, which can further reduce filler agglomeration and porosity between filler and resin matrix compared to other lubricants commonly used in the art; 7. By cryogenically pulverizing, particles with a D50 particle size of 30-100 micrometers are obtained, which allows the filler to be uniformly dispersed in the resin matrix, promoting nucleation and improving wear resistance.

[0028] Secondly, high-density polyethylene is selected as the resin matrix. Its crystallinity is higher than that of low-density polyethylene and linear low-density polyethylene. Under the nucleation effect of nano-talc, it is easier to improve the density of the resin and reduce the air or bubbles in the resin matrix. During the high-temperature cross-linking process, it is not easy to swell, and the resin will not produce bubbles or gaps that are suitable for water tree growth.

[0029] Third, short-cut basalt fibers with surface modification by vinyl silane coupling agent are introduced into the masterbatch of the present invention. The basalt fibers have strong bonding with the resin matrix, which improves wear resistance while reducing voids and bubbles, and improves the wear resistance of the sheath while maintaining good water tree resistance. Attached Figure Description

[0030] Figure 1 : Schematic diagram of the cross-section of a single-core 6~35kV water-resistant copper core cross-linked polyethylene insulated cable. 1 is the copper core, 2 is the semi-conductive shielding layer, 3 is the cross-linked polyethylene water-resistant insulation layer, 4 is the insulating shielding layer, 5 is the metal shielding layer, 6 is the insulation core of the single-core cable, and in sequence, the isolation sleeve, 9 is the metal armor layer, and 10 is the cross-linked polyethylene water-resistant sheath. Detailed Implementation

[0031] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can understand the advantages and effects of the present invention from the content disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and various details in this specification can also be modified and changed based on different viewpoints and applications without departing from the spirit of the present invention. Furthermore, the accompanying drawings of the present invention are for simple illustrative purposes only and are not depictions of actual dimensions; this is stated beforehand. The following embodiments will further describe the relevant technical content of the present invention in detail, but the disclosed content is not intended to limit the scope of protection of the present invention.

[0032] The raw materials used in the experiment came from the following sources:

[0033] High-density polyethylene: HDPE 5000S, density 0.951 g / cm³ 3 Purchased from Sinopec Lanzhou Petrochemical.

[0034] Low-density polyethylene: LDPE 951-000, density 0.918 g / cm³ 3 Purchased from Maoming Petrochemical.

[0035] Linear low-density polyethylene: LLDPE 7042, density 0.920 g / cm³ 3 Purchased from Dushanzi Petrochemical.

[0036] Ultra-high molecular weight polyethylene: Sinopec, PE-UHMW MI, viscosity-average molecular weight 1.5 million.

[0037] Dicumyl peroxide: Commercially available.

[0038] Short-cut basalt fibers: length range 2-8mm, diameter 10-13 micrometers, purchased from Sichuan Aerospace Tuoxin Basalt Industry Co., Ltd.

[0039] Short-cut fiberglass: length range 3~6mm, diameter 13 micrometers, purchased from China Jushi.

[0040] Nano talc: D50≤650nm, HTP Ultra 5L, purchased from Liaoning Aihai Yimi Mining.

[0041] Micronized talc powder: AH-1250, with a screening D50 particle size of 10 microns, purchased from Guangxi Longsheng Huamei Talc Development Co., Ltd.

[0042] Calcium carbonate: D50 = 16 micrometers, commercially available.

[0043] Montmorillonite: Sodium-based montmorillonite with a D50 particle size of 15 micrometers was purchased from Zhejiang Fenghong.

[0044] Sorbitol: DBS, commercially available.

[0045] Vinylsilane coupling agent: vinyltrimethoxysilane, purchased from Aladdin.

[0046] Aminosilane coupling agent: KH-550, aminopropyltriethoxysilane, commercially available.

[0047] Polyethylene wax: AC-617A, melting point 105℃, purchased from Honeywell.

[0048] Pentaerythritol stearate: melting point 64℃, PETS, commercially available.

[0049] Calcium stearate: melting point 150℃, commercially available.

[0050] Antioxidant: Antioxidant 1010: Antioxidant 168 in a mass ratio of 3:1, commercially available.

[0051] The following examples and comparative cases use a single-core 35kV water-tree resistant copper core cross-linked polyethylene insulated cable as an example. The copper core has 60 wires per section, the semi-conductive shielding layer is 0.8mm thick, the cross-linked polyethylene water-tree resistant insulation layer is 10.5mm thick, the insulating shielding layer is 0.8mm thick, the copper fiber braided tape consists of loosely wound soft copper wire and reverse-wrapped copper tape tightly bound together, the insulating sleeve is 2.2mm thick, the non-magnetic stainless steel tape is 0.5mm thick and 45mm wide, and the sheath is 3.2mm thick. The cross-linking conditions are 295℃ and nitrogen pressure 1MPa.

[0052] Test method:

[0053] (1) Test method for water tree resistance: Cross-linked polyethylene waterproof tree insulation layer material and cross-linked polyethylene waterproof tree abrasion resistant sheath material were respectively prepared into cross-linked standard circular specimens. According to the method in ASTM D6097a "Standard Test Method for Relative Resistance to Radial Water Tree Growth of Solid Insulating Materials", water tree resistance is expressed by the water tree growth resistance RWTG formula, RWTG=L÷WTL; L=3.2mm (distance between the needle plate electrodes, i.e., the thickness of the specimen), WTL is the maximum length of the water tree. The test was performed 3 times and the average value was taken.

[0054] (2) Outer sheath abrasion test: Using a 1000mm long finished cable as the test sample, apply a 270N force to abrade it 25 times (scraper stroke 800mm, speed 200mm / s) and check for indentations, gaps, or cracks in the sheath; then use a non-magnetic stainless steel strip as the negative electrode and apply a 20kV DC voltage for 1 minute between the negative electrode and the salt solution to test for breakdown. Gaps, cracks, or even breakdown indicate failure, while only slight indentations indicate acceptance.

[0055] Table 1. Formulation (%) of the filler masterbatch used in the examples and comparative examples

[0056]

[0057] Continued from Table 1:

[0058]

[0059] Preparation process of filler masterbatch A1~A11 / A14~A16: First, the filler and coupling agent (diluted 10 times with ethanol / water solution at a volume ratio of 1:9) are mixed and then mixed in a mixer at 80°C for 1 hour. Then, it is extruded and granulated with lubricant and polyethylene extruder. The barrel temperature is set to 125°C / 135°C / 120°C. After cooling, it is frozen with liquid nitrogen and then crushed and sieved by a low temperature pulverizer.

[0060] Preparation process of filler masterbatch A12: The difference from masterbatch A1 is that the mixing temperature is 50℃.

[0061] Preparation process of filler masterbatch A13: First, nano talc powder and vinyl silane coupling agent (diluted 10 times with ethanol / water solution at a volume ratio of 1:9) are mixed evenly and kneaded at 80°C for 1 hour in a mixer. Then, it is extruded with polyethylene wax and high-density polyethylene in a extruder with the barrel temperature set to 125°C / 135°C / 120°C. After cooling and pelletizing, masterbatch with a diameter of about 3 mm is obtained (excluding liquid nitrogen cryogenic pulverization process).

[0062] Table 2. Formulation (%) and water-resistant properties of cross-linked polyethylene waterproof insulation layers in the examples and comparative examples.

[0063]

[0064] Continued from Table 2:

[0065]

[0066] Continued from Table 2:

[0067]

[0068] The preparation method of the cross-linked polyethylene waterproof resin insulation material of Example A and Comparative Examples A1~A19 is as follows: the components are mixed and then extruded and granulated by a twin-screw extruder, and the extrusion temperature range is 120~140℃.

[0069] Examples A1-A2 and Comparative Example A19 demonstrate that the cross-linked polyethylene waterproof resin insulation layer of the present invention has good water-resistant resin resistance.

[0070] Comparative Example A1 shows that the talc powder dispersibility is poor when the content of vinylsilane coupling agent is too low, and the improvement is not significant compared with Comparative Example A19.

[0071] Comparative Example A2 shows that when the content of vinyl silane coupling agent is too high, the surface of nano talc powder will be over-grafted and modified, inhibiting nucleation and causing the density of the polyethylene resin matrix to decrease. During the high-temperature crosslinking process, the matrix resin is prone to swelling, resulting in poor water-tree resistance. Compared with Comparative Example A19, the improvement is very small.

[0072] Comparative examples A3 to A5 represent coating resins for which ultra-high molecular weight polyethylene, low-density polyethylene, and linear low-density polyethylene cannot replace high-density polyethylene as filler masterbatch.

[0073] Comparative Example A6 shows that aminosilane coupling agents cannot replace vinylsilane coupling agents.

[0074] Comparative Examples A7 / A8 indicate that commonly used lubricants in polyethylene, such as pentaerythritol stearate and calcium stearate, cannot replace polyethylene wax. Furthermore, calcium stearate is better than pentaerythritol stearate, possibly because calcium stearate, with its higher melting point, can play a slight nucleating role in high-density polyethylene.

[0075] Comparative Example A9 shows that when the particle size of the high-density polyethylene-coated nano-talc masterbatch is too large, the water-tree resistance performance decreases significantly.

[0076] Comparative Example A10 shows that the preparation process of the high-density polyethylene coated nano-talc masterbatch of the present invention is one of the key processes.

[0077] Similar to Comparative Example A9, when the particle size of the masterbatch is too large (particles with a diameter of 3 mm), the water-tree resistance of Comparative Example A11 is significantly lower than that of Comparative Example A19, indicating that the dispersibility is too poor.

[0078] Comparative Examples A12 / A13 indicate that due to the low crystallinity of low-density polyethylene and linear low-density polyethylene, even the addition of masterbatch obtained by the method of this invention does not achieve satisfactory results. Further experiments revealed that even with the addition of filler masterbatch A1, the water-tree resistance RWTG did not exceed 20.

[0079] Comparative Examples A14 / A15 / A16 show that micronized talc powder and calcium carbonate, commonly used in polyethylene, have limited effect on improving water tree resistance. However, when montmorillonite is used, its layered microstructure results in poor nucleation ability and easy aggregation, which reduces water tree resistance.

[0080] Comparative Examples A17 / A18 show that when the amount of high-density polyethylene-coated nano-talc masterbatch added is too little or too much, the improvement in water tree resistance is not significant.

[0081] Comparative Example A20: 96.2% high-density polyethylene, 1.5% dicumyl peroxide, 1.5% nano-talc, 0.024% vinyl silane coupling agent, 0.276% polyethylene wax, and 0.5% antioxidant. The preparation process was as follows: first, nano-talc and vinyl silane coupling agent (diluted 10 times with a 1:9 volume ratio ethanol / water solution) were mixed evenly and then kneaded at 80°C for 1 hour. Then, it was blended with other raw materials and extruded to obtain a cross-linked polyethylene waterproof resin insulation layer material. The extrusion temperature range was 120~140°C. Testing showed WTL=0.21mm and RWTG=15.2. It is evident that if the nano-talc is not pretreated with the vinyl silane coupling agent to prepare micron-sized masterbatch, the RWTG will actually decrease compared to Comparative Example A19.

[0082] Comparative Example A21: 97% high-density polyethylene, 1.5% dicumyl peroxide, 0.5% sorbitol, 0.5% polyethylene wax, and 0.5% antioxidant. The preparation process was as follows: the components were mixed evenly and extruded through a twin-screw extruder to obtain a cross-linked polyethylene waterproof resin insulation layer. The extrusion temperature range was 120~140℃. Testing showed WTL=0.18mm and RWTG=17.8. It is evident that sorbitol, a commonly used organic nucleating agent in this field, has insufficient anti-water-tree properties.

[0083] Table 3. Formulation (%) of the filler masterbatch used in the examples and comparative examples

[0084]

[0085] The preparation process of filler masterbatches B1~B7 is as follows: Nano talc powder and vinyl silane coupling agent (diluted 10 times with ethanol / water solution at a volume ratio of 1:9) are mixed evenly and then mixed at 80°C for 1 hour using a mixer; chopped basalt fiber (or glass fiber) and vinyl silane coupling agent (diluted 10 times with ethanol / water solution at a volume ratio of 1:9) are mixed evenly and then mixed at 80°C for 1 hour using a mixer; finally, high-density polyethylene and polyethylene wax are extruded and granulated using an extruder, with the barrel temperature set to 125°C / 135°C / 120°C, and after cooling, the mixture is cryogenically pulverized and sieved using liquid nitrogen.

[0086] The preparation process of filler masterbatch B8 differs from that of filler masterbatch B1 in that the mixing temperature is 50℃.

[0087] Preparation process of filler masterbatch B9: Nano talc powder, short-cut basalt fiber, vinyl silane coupling agent, polyethylene wax, and high-density polyethylene are extruded and granulated through an extruder. The barrel temperature is set to 125℃ / 135℃ / 120℃. After cooling, the mixture is cryogenically pulverized by liquid nitrogen and then sieved.

[0088] Table 4. Formulation (%) of cross-linked polyethylene waterproof and abrasion-resistant sheathing in the examples and comparative examples, and test results of abrasion resistance and water-tree resistance.

[0089]

[0090] The preparation method of the cross-linked polyethylene waterproof and wear-resistant sheathing material in Example B and Comparative Examples B1~B8 is as follows: the components are mixed and then extruded and granulated by a twin-screw extruder, with an extrusion temperature range of 120~140℃.

[0091] Examples B1-B2 and Comparative Example B8 demonstrate that the cross-linked polyethylene waterproof tree-resistant abrasion-resistant sheath of the present invention has satisfactory abrasion resistance and can achieve water tree resistance with RWTG > 20.

[0092] Comparative Example B1 shows that although glass fiber can also significantly improve wear resistance, its water-tree resistance is somewhat worse than that of basalt fiber.

[0093] Comparative Examples B2 / B3 show that when the weight ratio of vinyl silane coupling agent to talc is too low or too high, the water-tree resistance is not significantly improved compared to Comparative Example B8.

[0094] Comparative Example B4 shows that when the content of short-cut basalt fiber is too high, although it can further improve abrasion resistance, the water-tree resistance is significantly reduced.

[0095] Comparative Example B5 shows that when the particle size of the masterbatch is too large, the resistance to water treeing is poor.

[0096] Comparative Examples B6 / B7 illustrate that the preparation process of the high-density polyethylene coated nano-talc powder and basalt fiber masterbatch in this application is a key factor, especially the pretreatment method for the nano-talc powder and basalt fiber masterbatch.

[0097] Comparison with B9: High-density polyethylene 93%, dicumyl peroxide 2%, sorbitol 1%, antioxidant 0.5%, chopped basalt fiber 3%, polyethylene wax 0.5%. Preparation process: All components are mixed evenly and extruded through a twin-screw extruder to obtain cross-linked polyethylene waterproof and abrasion-resistant sheath material. The extrusion temperature range is 120~140℃. Testing showed that the abrasion resistance was qualified, WTL=0.22mm, RWTG=14.5. This indicates that the commonly used organic nucleating agent (sorbitol) in this field has poor water-tree resistance.

Claims

1. A 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable, characterized in that, Cables are made up of a single insulated core or multiple insulated cores twisted together. The insulated core consists of a copper wire core, a semi-conductive shielding layer, a cross-linked polyethylene waterproof resin insulation layer, an insulating shielding layer, and a metal shielding layer from the inside out. Outside the insulated core of a single-core cable are an isolation sheath, a metal armor layer, and a cross-linked polyethylene waterproof resin sheath. The multi-core cable consists of, in order, a filler layer, a binding tape, a metal armor layer, and a cross-linked polyethylene waterproof sheath outside the insulated core; The raw materials of the cross-linked polyethylene waterproof resin insulation layer, calculated by weight percentage, include: 92-97.5% high-density polyethylene, 1-2% peroxidation cross-linking initiator, 1-5% high-density polyethylene coated with nano-talc masterbatch with a D50 particle size of 30-100 micrometers, 0.5-1% antioxidant, and 0-1% cross-linking aid; the raw materials of the cross-linked polyethylene waterproof resin wear-resistant sheath, calculated by weight percentage, include: 82-94% high-density polyethylene, 0.5-2% peroxidation cross-linking initiator, 5-15% high-density polyethylene coated with nano-talc and short-cut basalt fiber masterbatch with a D50 particle size of 30-100 micrometers, 0.5-1% antioxidant, 0-2% additive, and 0-1% cross-linking aid.

2. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 1, characterized in that, The peroxidation crosslinking initiator is one or more of bis-tert-butyl peroxide, diisopropylbenzene peroxide, diisopropylbenzene peroxide, diisopropylbenzene peroxide, and lauroyl peroxide; the antioxidant is a hindered phenolic antioxidant and a phosphite antioxidant in a mass ratio of (2~4):1; the additive is an anti-ultraviolet agent, colorant, or pigment; the crosslinking aid is one or more of triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate, and trimethylolpropane triacrylate; the density range of the high-density polyethylene is 0.940~0.970 g / cm³. 3 .

3. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 1, characterized in that, The weight percentage of high-density polyethylene coated nano-talc masterbatch with D50 particle size of 30~100 micrometers includes: 40~50% high-density polyethylene, 0.3~0.8% vinyl silane coupling agent, 40~50% nano-talc powder, and 5~10% polyethylene wax. The weight ratio of nano-talc powder to vinyl silane coupling agent is (60~150):

1.

4. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 3, characterized in that, The preparation process of the high-density polyethylene coated nano-talc masterbatch with D50 particle size of 30~100 micrometers is as follows: first, nano-talc powder and vinyl silane coupling agent are mixed in a mixer at 60~90℃ for 0.5~3 hours, and then extruded and granulated with polyethylene wax and high-density polyethylene through an extruder. The barrel temperature range is 120~140℃. After cooling, it is obtained by freeze crushing and sieving.

5. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 1, characterized in that, The weight percentage of high-density polyethylene coated with nano-talc powder and short-cut basalt fiber masterbatch with D50 particle size of 30~100 micrometers is calculated as follows: 30~50% high-density polyethylene, 30~50% nano-talc powder, 5~10% short-cut basalt fiber, 1~2% vinyl silane coupling agent, and 5~10% polyethylene wax. The weight ratio of nano-talc powder to vinyl silane coupling agent is (60~150):

1.

6. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 5, characterized in that, The preparation process of the D50 high-density polyethylene coated nano-talc powder and short-cut basalt fiber masterbatch with a particle size of 30~100 micrometers is as follows: nano-talc powder and vinyl silane coupling agent are mixed in a mixer at 60~90℃ for 0.5~3 hours, and short-cut basalt fiber and vinyl silane coupling agent are mixed in a mixer at 60~90℃ for 0.5~3 hours. Then, high-density polyethylene and polyethylene wax are extruded and granulated through an extruder. The barrel temperature range is 120~140℃. After cooling, the product is obtained by freeze crushing and sieving.

7. The 6-35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claims 3-6, characterized in that, The vinyl silane coupling agent is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and vinyltritert-butylperoxysilane.

8. The 6~35kV water-tree resistant copper core cross-linked polyethylene insulated cable according to claim 1, characterized in that, The filler layer is either refractory filler or filler rope. The refractory filler is a near-circular refractory filler, and the filler rope is glass water-resistant yarn. The metal shielding layer is copper fiber tape.

9. A raw material for a cross-linked polyethylene waterproof resin insulation layer, characterized in that, The composition, by weight percentage, includes: 92-97.5% high-density polyethylene, 1-2% peroxidation crosslinking initiator, 1-5% high-density polyethylene-coated nano-talc masterbatch with a D50 particle size of 30-100 micrometers, and 0.5-1% antioxidant; wherein the high-density polyethylene in the high-density polyethylene-coated nano-talc masterbatch with a D50 particle size of 30-100 micrometers has a density range of 0.940-0.970 g / cm³. 3 The weight percentage of high-density polyethylene coated nano-talc masterbatch with D50 particle size of 30~100 micrometers includes: 40~50% high-density polyethylene, 0.3~0.8% vinyl silane coupling agent, 40~50% nano-talc, and 5~10% polyethylene wax. The weight ratio of nano-talc to vinyl silane coupling agent is (60~150):

1.

10. A raw material for a cross-linked polyethylene waterproof and wear-resistant sheath, characterized in that, The composition, by weight percentage, includes: 82-94% high-density polyethylene, 0.5-2% peroxidation crosslinking initiator, 5-15% high-density polyethylene coated with nano-talc powder and short-cut basalt fiber masterbatch with a D50 particle size of 30-100 micrometers, 0.5-1% antioxidant, and 0-2% additives; wherein the high-density polyethylene in the high-density polyethylene coated with nano-talc powder and short-cut basalt fiber masterbatch with a D50 particle size of 30-100 micrometers has a density range of 0.940-0.970 g / cm³. 3 The composition, calculated by weight percentage of high-density polyethylene coated with nano-talc powder and short-cut basalt fiber masterbatch with D50 particle size of 30-100 micrometers, includes: 30-50% high-density polyethylene, 30-50% nano-talc powder, 5-10% short-cut basalt fiber, 1-2% vinyl silane coupling agent, and 5-10% polyethylene wax. The weight ratio of nano-talc powder to vinyl silane coupling agent is (60-150):

1. The additives are UV stabilizers, colorants, or pigments.

Citation Information

Patent Citations

  • Water tree resistant polyolefin electrical insulation composition

    CN101104713A